ADAPTABILITY AND STABILITY STUDIES IN SUGAR CANE VARIETY - GonÃ§alves, Gustavo Menezes; Viana, Alexandre Pio; Entringer, Geovana Cremonini; Almeida, Livia Marcon (REVISTA DE AGRICULTURA, 2017)
The present study aimed to select the most productive clones of sugar cane that constitute the final phase of evaluation of clones. This crop has socioeconomic importance, for the production of ethanol as a renewable source of energy and less polluting than petroleum-based fuels. In this context, to release of new varieties can be one factor of greatest expression for the development of the sector. Twenty-four clones were evaluated in each mill, five of which were considered as standard and the other 19, as genotypes with potential for recommendation. The trait tons of pol per hectare (TPH) was assessed. Reduction for TPH was observed between cuts, with drop of was around 31.61% from the first to the third cut. Although differences were detected among the methodologies used, all of them contributed to better understanding of genotype x environment interaction, and are effective in recommending responsive genotypes.